MAKNA KURIKULUM TERHADAP TEORI TENTANG BELAJAR PADA PERUBAHAN PERILAKU ANAK DIDIK - Aslan Aslan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Education is life long. From the educational process carried out by humans, it cannot be separated from the changes that occur to students, both changes in the cognitive, affective and psychomotor domains. However, some of these changes have changed permanently and some are not, depending on the education provided by students, either through education in the family, school or community. In connection with the curriculum, that in essence education in the family environment, informal education that occurs in schools to tertiary institutions and education in the community through social institutions, cannot be separated from the curriculum that it goes through based on different experiences, so that understanding of the cognitive realm is also different. Whereas in the affective and psychomotor domains it depends on the experiences that students go through, so that behavior greatly influences social changes that occur in society